1996
DOI: 10.1007/s002849900105
|View full text |Cite
|
Sign up to set email alerts
|

The aggregation-mediated conjugation system of Bacillus thuringiensis subsp. israelensis: Host range and kinetics of transfer

Abstract: The aggregation-mediated conjugation system in Bacillus thuringiensis subsp. israelensis encoded on the plasmid pXO16 is characterized by the formation of aggregates when Agr+ and Agr- cells are socialized in exponential growth. Using the aggregation phenotypes, we have identified potential recipients of the aggregation-plasmid pXO16 among Bacillus cereus, Bacillus subtilis, Bacillus megaterium, Bacillus sphaericus, and 24 subspecies of B. thuringiensis. We found 14 Agr- strains, i.e., potential recipients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 48 publications
4
56
0
Order By: Relevance
“…Frequencies remained around 6.5 ϫ 10 Ϫ1 T/R until 4 h (data not shown). This confirmed previous kinetics studies performed with this plasmid where it was shown that pXO16 conjugation is efficient and fast (23).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Frequencies remained around 6.5 ϫ 10 Ϫ1 T/R until 4 h (data not shown). This confirmed previous kinetics studies performed with this plasmid where it was shown that pXO16 conjugation is efficient and fast (23).…”
Section: Resultssupporting
confidence: 91%
“…israelensis. This plasmid displays interesting features, such as fast and efficient transfer frequencies, a specific aggregation phenotype, and the ability to promote the transfer of nonmobilizable plasmids (2,3,4,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…israelensis cured of its three small circular plasmids . GBJ002 (Jensen et al, 1996), a B. thuringiensis sv. israelensis 4Q2-72-derived strain cured of all its plasmids, was used as an indicator strain for phage experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In reality, it is only the insect-toxic effect that differentiates the two species. The genes coding for insect toxins are found primarily on large plasmids in B. thuringiensis (5), and in the laboratory, these plasmids can be lost or transferred horizontally to other bacilli (16,17,28,30,47); hence, a B. thuringiensis strain can be transformed into a B. cereus strain and vice versa. We have previously isolated B. thuringiensis from the feces of exposed persons (29), and in this study, we have shown that commercial preparations of B. thuringiensis subsp.…”
Section: Discussionmentioning
confidence: 99%